Salmonella Genomic Island 1B Variant Found in a Sequence Type 117 Avian Pathogenic Escherichia coli Isolate - Max Laurence Cummins (American Society for Microbiology, 2019)
ABSTRACT Salmonella genomic island 1 (SGI1) is an integrative genetic island first described in Salmonella enterica serovars Typhimurium DT104 and Agona in 2000. Variants of it have since been described in multiple serovars of S. enterica, as well as in Proteus mirabilis, Acinetobacter baumannii, Morganella morganii, and several other genera. The island typically confers resistance to older, first-generation antimicrobials; however, some variants carry blaNDM-1, blaVEB-6, and blaCTX-M15 genes that encode resistance to frontline, clinically important antibiotics, including third-generation cephalosporins. Genome sequencing studies of avian pathogenic Escherichia coli (APEC) identified a sequence type 117 (ST117) isolate (AVC96) with genetic features found in SGI1. The complete genome sequence of AVC96 was assembled from a combination of Illumina and single-molecule real-time (SMRT) sequence data. Analysis of the AVC96 chromosome identified a variant of SGI1-B located 18 bp from the 3′ end of trmE, also known as the attB site, a known hot spot for the integration of genomic islands. This is the first report of SGI1 in wild-type E. coli. The variant, here named SGI1-B-Ec1, was otherwise unremarkable, apart from the identification of ISEc43 in open reading frame (ORF) S023. IMPORTANCE SGI1 and variants of it carry a variety of antimicrobial resistance genes, including those conferring resistance to extended-spectrum β-lactams and carbapenems, and have been found in diverse S. enterica serovars, Acinetobacter baumannii, and other members of the Enterobacteriaceae. SGI1 integrates into Gram-negative pathogenic bacteria by targeting a conserved site 18 bp from the 3′ end of trmE. For the first time, we describe a novel variant of SGI1 in an avian pathogenic Escherichia coli isolate. The presence of SGI1 in E. coli is significant because it represents yet another lateral gene transfer mechanism to enhancing the capacity of E. coli to acquire and propagate antimicrobial resistance and putative virulence genes. This finding underscores the importance of whole-genome sequencing (WGS) to microbial genomic epidemiology, particularly within a One Health context. Further studies are needed to determine how widespread SGI1 and variants of it may be in Australia.